2017
DOI: 10.5897/ajar2016.11958
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic determinants of hybrid maize adoption in Kenya

Abstract: Kenya has increasingly relied on modern agricultural technology to increase productivity since land extensification is no longer a feasible option to satisfy national food demands. Hybrid maize varieties have been one of the more successful technologies developed, responsible for dramatic yield increases in the developed world since World War II and more recently as an integral part of the Green Revolution. The purpose of this paper is to investigate the factors that affect the adoption of hybrid maize varieti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
4
2
0
Order By: Relevance
“…According to Rola-Rubzen et al (2020), social-cultural values and norms give men authority over decision-making and ownership of productive resources such as land. This could have enhanced their adoption of seed multiplication agri-enterprise as compared to women.These findings are consistent with Wang et al (2017), whose study found a results of Wang et al (2017), who abserved that farmers with college and higher education levels had a higher probability of adopting hybrid maize; and concluded that educated farmers were more likely to purchase hybrid seed and observe agronomic practices. Educated farmers tend to have comparatively greater access to information than their illiterate counterparts, thus increasing their level of awareness to new technology and entrepreneurial opportunities.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…According to Rola-Rubzen et al (2020), social-cultural values and norms give men authority over decision-making and ownership of productive resources such as land. This could have enhanced their adoption of seed multiplication agri-enterprise as compared to women.These findings are consistent with Wang et al (2017), whose study found a results of Wang et al (2017), who abserved that farmers with college and higher education levels had a higher probability of adopting hybrid maize; and concluded that educated farmers were more likely to purchase hybrid seed and observe agronomic practices. Educated farmers tend to have comparatively greater access to information than their illiterate counterparts, thus increasing their level of awareness to new technology and entrepreneurial opportunities.…”
Section: Resultssupporting
confidence: 88%
“…Being a male farmer increased the log odds of being in higher adoption tendency stage of CSPMAE by 0.65, as compared to female farmers, ceteris paribus (Table 7). This could be attributed to gender roles defined by the society, whereby male gender is less confined to domestic jobs, hence giving them freedom to participate in several meetings and trainings, as postulated by Wang et al (2017). Such meetings may involve dissemination of useful information, which probably enhanced their uptake of CSPMAE.…”
Section: Resultsmentioning
confidence: 99%
“…Age with the coefficient of -0.052 revealed that one year increase in age decreased the logit in favor of adoption of hybrid maize variety by 5.2% and it might be due to the reason that aged people often are scared of unseen risks associated with the use of new technologies. The results are in accordance to Wang et al (2017), Sánchez-Tolendano et al (2018 as their research work revealed that young farmers are more adoptive to hybrid maize technology than the aged ones. A unit increase in education had a positive and significant effect on adoption of hybrid maize varieties and a unit increase in years of schooling increased the probability of adopting such varieties by 9.2%.…”
Section: Estimates Of Logistic Regressionsupporting
confidence: 88%
“…The estimates of marginal effects showed that almost all the explanatory variables were statistically significant at α= 0.05. Age with the predicted coefficient of -0.0076 showed the higher probability of adopting the hybrid maize technology by younger farmers than the aged ones and the results are in accordance to Wang et al (2017). An increase in household's land holdings and education level showed the 4.2% and 13.3% higher probability of adopting the hybrid maize technology and these results are in accordance to Sánchez-Tolendano et al (2018).…”
Section: Marginal Effectssupporting
confidence: 85%
“…Plant height, grain yield, and taste of maize meal were also rated better for DroughtTEGO hybrids (Table 2). Other studies have reported that farmers rated high grain yield, disease resistances, good grain milling quality, and drought tolerance to be the most important traits in adoption of new maize hybrids (Wang et al, 2017; Nyaligwa et al, 2016; Afriyie‐Debrah et al, 2018).…”
Section: Resultsmentioning
confidence: 99%